The mosque institution in history: Lessons for today - Omer, Spahic (s.n, 2012)
This research will critically explore the theme of the position and roles of the mosque institution in the course of Muslim history. Most relevant phases of Muslim history with most prominent geographical regions and history maker will be the focus of the research.